Synthesis and Physical Characterization of Manganese DioxideNanoparticles Using Leek Extract for Antibacterial Application - A. Hayder, Rand; Zainab J. Shanan, (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Manganese dioxide nanoparticles were synthesized by the green method using leek with Manganous Sulphate Monohydrate, (MnSO4.H2O) in an environmentally friendly manner. The obtained MnO2 particle was characterized by x-ray diffraction (XRD), field scanning electron microscopy (FESEM), atomic force microscopy (AFM), and (UV-Visible) spectroscopy. The X-ray diffraction pattern showed peaks belonging to manganese oxide nanoparticles; 34.07 nm is the average crystalline size. From the field-scanning electron microscopy (FESEM) image, the surface morphology shows that the nanoparticles are spherical and rocky in shape. An atomic force microscopy (AFM) atomic force microscope was used to show MnO2 NPs as agglomerated particles with an average diameter of (50.20) nm. The absorption spectrum of MnO2 nanoparticles was determined using UV-visible, and the energy band was measured to be (4.31) eV. The results show that the band gap energy increases with decreasing particle size. The antibacterial property of nanoparticles was observed. These materials' antibacterial effects were examined utilizing some common Gram-positive and Gram-negative bacteria. The synthesis of MnO2-NPs inhibited the growth of S. aureus, k. pneumoniae, and E. coli, with half-dilutions. MnO2-NPs have shown good inhibition for S. aureus and lower efficient antibacterial activity against the bacterial k. pneumonia and E. coli, and the higher activity was at a concentration of (1000μg/ml).